ANALISIS PENERAPAN MEDIA GAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Annisa Nurul Ilmi; Asep Sahrul Gunawan (STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in the IPAS subject at elementary schools, caused by the less optimal use of interesting and contextual learning media. Learning that is still teacher-centered makes students less active, easily bored, and experience difficulties in understanding the material. Picture media is considered an effective alternative because it can present information visually, helping students understand concepts more concretely and meaningfully. This study aims to analyze the implementation of picture media and its influence on students’ learning outcomes in the IPAS subject at elementary schools. The method used is a literature review by examining various scientific sources in the form of 12 journal articles indexed in SINTA, GARUDA, and Google Scholar, as well as 3 relevant reference books. The results of the study indicate that the implementation of picture media consistently has a positive impact on improving students’ learning outcomes. Picture media is able to increase students’ attention, motivation, and understanding of IPAS material. Therefore, picture media is effective for use in elementary school learning.